2019
DOI: 10.1177/1178638819866434
|View full text |Cite
|
Sign up to set email alerts
|

Primary Care and Food Bank Collaboration to Address Food Insecurity: A Pilot Randomized Trial

Abstract: Food insecurity is common in the United States and linked to poor control of conditions influenced by diet. We conducted a pilot randomized trial to test whether a novel partnership between a primary care practice and a municipal food bank would improve control of type 2 diabetes among patients with food insecurity. Participants received food bank produce delivered twice monthly to the practice site, brief teaching from a food bank dietitian, and home-based education from a community health worker. After 6 mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
155
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(159 citation statements)
references
References 29 publications
1
155
0
3
Order By: Relevance
“…All included studies (n = 35) had a screening and referral component and originated in the US ( Tables 1 and 2 ). Most screening and referral programs were implemented in pediatric clinics (n = 15) ( 21 , 26 , 29 , 30 , 34 37 , 39 , 43 , 47 , 49 , 50 , 54 , 55 ) and other primary care practices (n = 11) ( 22 , 23 , 25 , 27 , 28 , 31 , 32 , 38 , 40 , 41 , 53 ); the rest (n = 9) were in other settings ( 24 , 33 , 42 , 44 46 , 48 , 51 , 52 ). Included studies defined target populations by health conditions or behavioral risk factors (eg, patients with diabetes, or patients who smoke), and/or demographic characteristics (eg, age, sex).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All included studies (n = 35) had a screening and referral component and originated in the US ( Tables 1 and 2 ). Most screening and referral programs were implemented in pediatric clinics (n = 15) ( 21 , 26 , 29 , 30 , 34 37 , 39 , 43 , 47 , 49 , 50 , 54 , 55 ) and other primary care practices (n = 11) ( 22 , 23 , 25 , 27 , 28 , 31 , 32 , 38 , 40 , 41 , 53 ); the rest (n = 9) were in other settings ( 24 , 33 , 42 , 44 46 , 48 , 51 , 52 ). Included studies defined target populations by health conditions or behavioral risk factors (eg, patients with diabetes, or patients who smoke), and/or demographic characteristics (eg, age, sex).…”
Section: Resultsmentioning
confidence: 99%
“…The social needs addressed included education (eg, poor literacy, health education) ( 23 , 24 , 27 , 33 , 38 41 , 49 – 52 , 55 ), unemployment and income insecurity (eg, vocational training, financial burden) ( 23 , 24 , 26 , 31 , 33 , 36 , 38 41 , 43 , 48 – 52 , 55 ), food insecurity ( 22 24 , 26 , 28 , 30 , 31 , 35 41 , 43 , 45 47 , 49 51 , 53 55 ), housing insecurity (eg, poor housing conditions, homelessness) ( 23 , 24 , 26 , 29 , 31 , 35 , 36 , 38 41 , 43 , 49 – 52 , 55 ), interpersonal safety (eg, intimate partner violence) ( 21 , 24 , 32 36 , 38 , 39 , 43 , 44 , 49 , 55 ), transportation to health care site ( 24 , 31 , 35 , 39 , 41 , 50 , 51 , 55 <...>…”
Section: Resultsmentioning
confidence: 99%
“…The score increased significantly (6.98 ± 1.74 vs. 7.53 ± 1.68, p < 0.001), and could be suggestive of an amelioration of dietary habits. Dietary screening and nutritional intervention have often been useful for the management of chronic conditions, such as obesity and diabetes, and to improve lifestyle [41][42][43]. In this population, the consumption of healthy food groups also increased, such as vegetables (p = 0.003) and nuts (p = 0.037), and the consumption of red and processed meats decreased simultaneously (p = 0.004).…”
Section: Discussionmentioning
confidence: 99%
“…A pilot study of a medically tailored meal intervention found improved diet quality among individuals with type 2 diabetes and food insecurity [ 36 ]. Furthermore, a small randomized trial (n = 43 at follow-up) found a large decrease in hemoglobin A1c (1.4 percentage points, P = .01) with a collaborative primary care and food bank intervention [ 37 ]. However, a larger randomized trial (n = 568) of a combined food provision and diabetes self-management education intervention based at food pantries did not find a decrease in hemoglobin A1c (difference between intervention and control group 0.24 percentage points; 95% CI −0.09, 0.58), though it did find a reduction in food insecurity (risk ratio 0.85.…”
Section: Resultsmentioning
confidence: 99%